Characterization of acid burn victims in two selected health facilities in Dhaka city - Islam, Md Jahidul; Uddin, MM Jalal; Hossain, Md Shahadat; Amin, Md Ruhul; Khandaker, Md Nuruzzaman; Rahman, AZM Mahfuzur; Taher, Abu (Bangladesh Medical Journal, 2014)
This descriptive cross sectional study was carried out in Dhaka Medical College Hospital (DMCH) and Acid Survivors Foundation (ASF), Dhaka from January to June 2010 among the acid burn patients admitted in DMCH and acid burn victims taking services from ASF to find out the socio-demographic characteristics, physical extent of injury, and to identify the reasons behind acid burn in selected institution in Dhaka city. A total of 112 samples were taken purposively and data were collected by face to face interview. Among the respondents most were female (58.04%). Mean age was 20.3 years and most came from rural and semi-urban areas (91.82%)l. Most of the incident occurred at the mid-night and at the time of sleeping (69.09%). 23% of the respondents lost their partial or full eye sight or hearing or both. Post burn complications developed in old burn patients 75.8%. Most of the victims (83%) faced various type of problems. Among the respondents, 65.2% suffered from superficial burn, 31.2% from mixed burn and 3.6% from deep burn. About 15.2% suffered from > 20% of total Body Surface (TBSA) burn. The main cause of acid burn was intentional (98.2%). Only 1.8% was accidental. In the female the intentional causes were presence at the site (21.9%), marriage proposal rejection (15.6%). In case of male the main causes were personal enmity (30.4%), presence at the site (28.3%). DOI: http://dx.doi.org/10.3329/bmj.v43i2.21391 Bangladesh Med J. 2014 May; 43 (2): 94-99